Evaluation of changes somatic features and motor skills of high school students from Kruszwica. - Cieslicka Miroslawa.; Napierala Marek.; Stankiewicz Blazej.; Iermakov Sergii. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2012)
Introduction. The study of the physical development of children and youth have quite a rich tradition. Conducted observations show that standard of living is very different in different regions of the country. The purpose of physical education is not only to improve the body of a young man, but also providing it with the knowledge and skills related to physical education. The aim of this study was to assess the state of development of somatic children aged 13 - 14 years of high school in Kruszwica, determine the level of their motor skills and evaluation of somatic sexual dimorphism. And the answer: if holiday break contributed to changes somatic features and motor skills of subjects. Materials and methods. The study was conducted twice: before the summer (June) and after the summer break, and have them included 72 students (39 boys and 33 girls) aged 13 - 14 years. Physical development determined on the somatic features: height and weight, efficiency of the motor, in turn, on the basis of level of skills and mobility. Habit of body students characterized using the Rohrer index. To determine the motor of subjects used trials of the International Physical Fitness Test. Results and conclusions. Analysis of the results allows to draw the following conclusions: •After holiday break students are higher and heavier than before the holidays. •After holiday break increased motor skills of both sexes in the strength of the abdominal muscles, but only in boys increase the explosive power in the legs and improve their speed. •Boys achieved better results after holiday break than girls in testing the speed and explosive power tests of legs. •According to Mollison Index compared characteristics of somatic and motor skills before summer the most varied of agility course and body height, after holidays: the explosive power of the legs and body height. •The impact of the summer break has not affected to changes in somatic and motor skills of the young people